Building a brighter future: the crucial role of character education in Malaysia’s education system - Muhammad Hafizi, Mardiah Hafizah; Kamarudin, Nurzatulshima; Mohamad Ibrahim, Nursakinah (Human Resource Management Academic Research Society, 2024)
As Malaysia continues to develop economically and socially, the nation's education system is pivotal in shaping a future where individuals are not only academically proficient but also imbued with strong moral values. Character education, which focuses on developing virtues such as integrity, responsibility, and empathy, plays a critical role in this vision. This article explores the importance of character education education in Malaysia's changing educational environment. Recognizing the ongoing difficulties faced by the country's education system, such as decreasing aca-demic achievement and social issues. It assesses the current status of character education in Malaysia, emphasiz-ing its inclusion in the national curriculum and the obstacles encountered during its implementation. Drawing on research results and comparisons with neighboring countries like Indonesia, this article identifies critical factors that affect how effective programs for character education are. These encompass a variety of cultural influences, policy structures, family and community engagement, and integration of Islamic principles. By addressing these multifacet-ed challenges and taking advantage of opportunities for cooperation and cultural diversity, Malaysia can effectively incorporate moral education into its schools to nurture morally upright individuals who are equipped to handle today's complexities. Ultimately, prioritizing moral education is crucial for advancing Malaysia's educational system and promoting societal unity while laying a foundation for a more ethically excellent future.